Experiential Learning in Business Communication: Starting a Peer-Reviewed Student Journal and Podcast - Richardson, Marianna E.; Stenquist, Ryan; Stenquist, Jenny (International Dialogues on Education Journal, 2019)
Ancient Greeks such as Plato, Socrates, and Aristotle realized the need for combining intellectual, theoretical learning with practical, real-world experiences. Modern educational theorists continue to make similar pleas for the need of a more holistic and experiential view of education. To promote experiential learning in business communication, Brigham Young University – Provo (BYU) started a peer-reviewed student journal and podcast for business students. The students’ experiences mirror Kolb’s experiential learning theory cycle (1984) and Mezirow’s theories on critical reflection and transformative learning, (1990, 1998, 2000). Students’ reflective comments were reviewed using Morris’ (2019) five characteristics of concrete learning experiences. Additionally, student ratings for this course are compared to other business management courses at BYU. These comparisons illustrate the high rating students give experiential learning courses. As the journal and podcast continue to grow in popularity, the opportunities for students have also grown because the students are gaining practical experience for future careers.